Закономірності зміни газоносності вугільних пластів та вмісних порід у зв’язку з глибиною залягання (на прикладі Львісько-Волинського басейну) - Бучинська, І.В. (Геотехническая механика, 2010)
Проанализирована газоносность пород и пластов углей одного достаточно небольшого
района (Тягловское месторождение Львовско-Волинского бассейна), что дало возможность
делать выводы о характере ее изменений с глубиной, не беря во внимание дополнительное
влияние тектоники. Установлено, что природная газоносность углей с глубиной увеличивается, а песчаников – уменьшается, что обусловлено разными формами нахождения газов. We have analysed a gas-bearing potential of rocks and coabeds from one rather small region
(the Tyagliv field of the Lviv-Vjlyn Basin) that enabled us to make conclusions about the character
of its changers with depth, not taking into account the additional influence of tectonics. It was established that natural gas-bearing potential of coal increases with a depth, and natural gas-bearing potential of sandstones decreases that depends on different forms of gas existence.